1. CASE SERIES OF SEXUAL DEVELOPMENT DISORDERS CAUSE BY GONADAL DYSGENESIS AT VIETDUC UNIVERSITY HOSPITAL IN 2015-2023 (Vietnam Journal of Community Medicine, 2024)
Background: Gonadal dysgenesis is a condition of the genital gland that is underdeveloped during the fetal period, which causes partial or total reduction in the production of genital hormones that cause sexual development disorders, infertility. Genital dysfunction is common in Turner syndrome (karyotype 45,X) or Klinefelter syndrome (47,XXY), and also in those with karyotype 46,XX or 46,XY or 45,X/46XY.Objects and method: This study is to describes 13 clinical cases of of gonadal dysgenesis in the Vietduc hospital from 2015 to 2023.Results: There were seven patients with complete gonadal dysgenesis and six patients partial gonadal dysgenesis, in which five patients 45,X/46,XY; four patients 46,XY, three patient Klinefelter with 47,XXY and one patient with 46,XX. Seven with female genitalia, breast and pubic hair were undeveloped, primary amenorrhea in adulthood. Five cases phenotype man with normal penis, one or two testes in scrotum, delayed puberty and azoospermia. One case was ambiguous genitalia. While concentration of testosterone and estradiol were lower than normal, LH and FSH were higher than normal.Conclusion: Gonadal dysgenesis occurs in those with chromosomes 46,XX or 46,XY, or 47,XXY ormosaic chromosome 45,X/46,XY, characterizing with poor or undeveloped genital glands, no signs of puberty or late puberty, amenorrhea and primary infertility.
Keywords: Gonadal dysgenesis, late puberty, primary amenorrhea.